Cannibalism in Eurasian otters ( Lutra lutra) - Calvo‐Fernandez, Cristina; Sorribes, Elisa L.; Garrido‐Moreno, Jesús; Martín‐Maldonado, Bárbara (River Research and Applications, 2024)
Abstract The Eurasian otter, Lutra lutra , faced adversity in Europe in the 1950s and 1960s due to hunting, declining fish populations and the American mink invasion. Slow recovery since the 1970s led to a ‘Near Threatened’ in the IUCN Red List status, but recent pollution, fishing pressure and habitat loss caused slight population declines. Otters, known for aquatic habits, are mainly piscivorous and exhibit solitaire or social behaviours. Infanticide with parent‐offspring cannibalism has been previously reported in otter species, but although cannibalism has been suggested, it has not been documented before. This study presents the first documented case of cannibalism among free‐living Eurasian otters observed in northern Norway. Some authors described cannibalism as an opportunistic resource‐efficient behaviour in several mammal species, offering benefits like weight gain and reduced competition, challenging the view of adverse health effects. Factors leading to otter cannibalism include ecological changes, resource competition with other species and global warming and overfishing practices contributing to increased otter competition. Further studies will be vital to answering intriguing questions about the implications of cannibalism for otter conservation.